Environmental law in ukraine: present and prospects - YASHCHUK, Sergii (Journal of Education, Technology and Computer Science, 2013)
The state policy in the field of ecology should be based on sustainable systemof law, legal acts, norms, but this system, especially during the transitionshould be flexible, that is able to respond quickly on changes of surroundingcomponents, to be able to adapt to changes of too complex environment. Andthis is very effective means for overcoming the environmental crisis and ensuringthe environmental function of the state.